Evaluating serum level of thymidylate synthase in post burn keloid patients before and after intralesional injection of 5-fluorouracil - Noha Ezzat Mohamad; Talal Ahmed Abd El Raheem; Rania Hosny Mahmoud; Nehal Osama Hamed (SAGE Publishing, 2022)
Background Keloids are fibrous lesions formed at the site of trauma due to types I and III collagen irregular production. The presence of thymidylate synthase (TS) is a must for DNA synthesis and repairs causing cell death. 5-fluorouracil (5-FU) is a fluorinated pyrimidine analogue acting as an anti-metabolic agent that inhibits thymidylate synthase and interferes with ribo-nucleic acid (RNA) synthesis. Objectives we aimed to evaluate the level of thymidylate synthase in post burn keloid patients before and after intralesional injection of 5-fluorouracil. Methods The study included 20 keloid patients and 20 healthy subjects as a control. Serum TS was estimated using commercially available enzyme-linked immunosorbent assay (ELISA) kits before and after treatment with 5-fluorouracil. Results There was a statistically significant difference in TS levels before and after 5-FU treatment (p < 0.05). Also, results have shown that 5-FU injection has good satisfactory results in treatment of keloid causing reduction in scar volume and symptoms improvement (90% of the patients improved). On the other hand, there was no statistically significant difference in TS levels and the outcomes of the treatment. Conclusion Our findings suggest that intralesional 5-FU injection in keloid has very satisfactory results. However, thymidylate synthase enzyme has a minimal role in evaluating the treatment of keloid, so further studies are required to elaborate the relation between this enzyme and keloid scars.